Efektivitas seduhan kayu manis terhadap kadar gula darah pada diabetes melitus tipe 2 di Puskesmas Langsa Barat - Nora Hayani; Suryati B; Zulkarnaini Zulkarnaini; Azwarni Azwarni; Yuni Ramadhani (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Diabetes mellitus is a disease that still threatens human life in the world. One of the non-pharmacological therapies to reduce blood sugar levels in patients with diabetes mellitus is cinnamon because it is a kitchen spice that is easily available.Objectives: This study is to test the effectiveness of cinnamon brew on reducing blood sugar levels in patients with type 2 diabetes mellitus in the Langsa Barat Health Center Working Area.Methods: This study used a quasi experiment method, the total sample of 88 respondents was divided into two groups, namely the intervention group giving cinnamon and the control group given education. The research was conducted in the working area of the West Langsa Health Center on May 1 - July 22, 2024. Data collection collaborated with the prolanis and PTM managers of the puskesmas to obtain data on diabetics, the implementation of interventions was carried out at the puskesmas and respondents' homes, with 2 times a day as much as 5 grams routinely for 7 days. Data were analyzed using the Paired Sample T-test.Results: : After the intervention of giving cinnamon, it was found that there was a decrease in blood sugar on day 3 (three), and after the intervention on day 7 (seven) it was found that there was a decrease in blood sugar for respondents with a p value of 0,000, while for the control group there was no decrease in blood sugar levels.Conclusion: Based on this study, cinnamon steeping intervention can have the effect of reducing blood sugar levels in patients with diabetes mellitus when consumed regularly, thus providing an option for diabetics to consume cinnamon as an alternative therapy option to lower blood glucose.